Evaluation of Strategic Human Resource Management in Local Authorities: A Focus on Organizational Culture and Job Motivation - Vegas-Gallo, Edwin (2024)
The strategic management of human resources in organizations is fundamental due to the competitive demands of the markets, which is why an excellent organizational culture must be maintained to increase workers' motivation. This study aims to provide specific recommendations to improve strategic human resource management in the context of municipalities, thus promoting a comprehensive transformation that increases the capacity to retain and attract valuable personnel. The research is quantitative and follows a correlational design. A questionnaire was administered to 112 employees of municipalities regarding the variable strategic human resources management with the dimensions of organizational culture, organizational climate, and personnel selection and the variable motivation with the dimensions of job satisfaction and work environment with a Cronbach's alpha reliability of 0.851. The results show that 65.18% of the workers consider that the organizational culture in the municipalities is fair, 67.86% of the workers highlight that the personnel selection capacity is inadequate, 53.75% express that the level of social relations in the organization is low, and 50% of the workers indicate that job satisfaction is fair. These results reflect that companies must increase their capacity to retain and attract stable and valuable personnel that fit the organization's profile.